Assessment of traditional procurement system in Nigeria: key challenges and proposed solutions - Garba, Mohammed Hamisu (2015)
Traditional procurement system is commonly used in Nigerian construction industry. However; despite the wide choice of other procurement system, there are numerous of key challenges that affects cost, time and quality of completed project. This challenge contributes negatively to both parties namely clients and contractor. To date, there are limited works that assess the key challenges of traditional procurement system in Nigeria which hinders the proposition of possible solutions to the problems. Hence, this research aims to identify the key challenges that are associated with traditional procurement in Nigerian construction industry with a view to identify areas of weakness and propose a solution. It also involves identification of the most frequent use of traditional procurement system. Structured questionnaire was distributed to 136 contractors that actively participated in the construction industry with 78 percent response rate. The use of mean, ranking, correlation and analysis of variance were used to analyses the data. The result shows that all the challenges have a significant relationship with the open tendering method. Further analysis also show that all the key challenges: Cost certainty, Time certainty, Build ability and Fragmentation of organizational interface have a significant relationship with one another. All the formulated solutions such as creation of unified project team, improvement in line of communication, early participation of contractor in design stage were found to be related to all the individual challenges and are therefore, suitable in overcoming all the key challenges.